CHRONIC MYELOID LEUKAEMIA IN A 14-YEAR-OLD CHILD: AN UNUSUAL CASE REPORT - Shah, Syed Yar Muhammad; Rahman Bahadar; Umer Zareen; Abdullah Zeb; Azizullah; Ahmed; Ameer Hamza; Rafiullha; Waqas Ahmad; Syed Yasir Hussain Gilani (Journal of Ayub Medical College Abbottabad, 2022)
Chronic myeloid leukaemia is a myeloproliferative stem cell disorder characterized by dysregulated production and proliferation of myeloid cells. Hallmark of the disease is the reciprocal translocation between chromosome 9 and 22 giving rise to an abnormal chromosome known as Philadelphia chromosome. Approximately 15% of all leukaemias are chronic myeloid leukaemia with a slight male predominance. This is a case of a 14-year-old boy with no premorbid presented with 4 months history of fatigue and shortness of breath on exertion. On examination patient was vitally stable. On general physical examination there was pallor and sternal tenderness. On abdominal examination spleen was palpable with a size of about 8cm. Respiratory, cardiovascular and musculoskeletal examination was unremarkable. Complete blood picture showed leukocytosis, low haemoglobin and normal platelets. Erythrocyte sedimentation rate was 65 mm/hr. Liver function tests, Renal function tests, Serum electrolytes, Urine routine examination and c-reactive protein were normal. Chest x-ray and Electrocardiography was normal. Peripheral blood smear showed neutrophils 56% with 3% lymphocytes, 1% blasts and retic count of 0.5%. Bone marrow biopsy was suggestive of chronic myeloid leukaemia which was confirmed by FISH and Cytogenetic studies.